(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
The article is devoted to advertising. It reveals the concept of "advertising language", the main purpose of which is to interest a large number of people to purchase a product or service. The development of the advertising language goes hand in hand with the development of the literary language. The article analyzes the means and techniques of creating advertising texts.